Penerapan Model Problem Based Learning Dalam Mmeningkatkan Hasil Belajar Peserta Didik Kelas IV UPTD SDN 04 Sungai Antuan - Ria Kemala Sari; Martina Iriani; Dela Zulfitri; Desri Wahyuni; Fadhila Yusri; Adi Warman (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research is motivated by the fact that in Islamic Religious Education learning so far, teachers still prefer to use lecture or conventional methods, which has an impact on students' reluctance to play an active role in learning, which causes less active learning and low academic results. When learning, teachers do not use interesting learning models, so that the student learning process does not go well. This research is classroom action research (CAR) which is carried out through collaboration between teachers and researchers, covering two cycles and the research subjects are 17 fourth grade students of UPTD SD Negeri 04 Sungai Antuan. The data were collected through data collection techniques in the form of observation data on student activities during the learning process and student learning outcomes. This study aims to apply an active problem-based learning model or commonly known as Problem Based Learning (PBL), to improve the learning outcomes of class IV Islamic Religious Education students at UPTD SD Negeri 04 Sungai Antuan. With a problem-based learning model, students can actively participate in learning and this model is one alternative solution that makes learning more active, effective, creative and enjoyable, expected to improve learning outcomes and performance. The results of the study showed that active learning using a problem-based learning model increased in each cycle. This was evident in the author's research conducted at the pre-cycle stage, the completion rate was only 35%. While after the problem-based learning model was applied in cycle 1, the graduation rate increased to 59%. In cycle 2 with the application of a similar model, the graduation rate increased to 94.1%. Based on the results of the study, it can be concluded that the application of the Problem Based Learning model can improve learning outcomes in the subject of Islamic Religious Education for class IV UPTD SD Negeri 04 Sungai Antuan.